Decreased tryptophan catabolism by placental indoleamine 2,3-dioxygenase in preeclampsia. - Kudo, Y; Boyd, C; Sargent, I; Redman, C (2003)
OBJECTIVE: Tryptophan degradation and depletion resulting from activation of indoleamine 2,3-dioxygenase is characteristic of inflammatory reactions and may control their intensity. Normal third-trimester pregnancy is characterized by a maternal systemic inflammatory response, which is more intense in preeclampsia. Therefore, we studied tryptophan metabolism in pregnant women, with or without preeclampsia, as well as expression and function of placental indoleamine 2,3-dioxygenase. STUDY DESIGN: Plasma concentrations of tryptophan and kynurenine in women with preeclampsia, appropriately matched women with normal pregnancy, and healthy nonpregnant women were measured. Placental enzymatic activity and messenger RNA (mRNA) expression level of indoleamine 2,3-dioxygenase were determined from the same placental material. Peripheral blood mononuclear cell proliferation was determined in medium conditioned by prior culture with villous tissue. RESULTS: The plasma ratio of kynurenine to tryptophan, an in vivo index of enzyme activity, was significantly increased compared with nonpregnant controls in normal pregnancy but not in preeclampsia. The activity and mRNA expression level of indoleamine 2,3-dioxygenase in term placentas were significantly lower in preeclampsia. Medium conditioned by culture of villous tissue explants of preeclampsia was less effective in inhibiting peripheral blood mononuclear cell proliferation compared with that of normal pregnancy. CONCLUSION: These observations suggest that in preeclampsia, reduced placental indoleamine 2,3-dioxygenase activity (and relatively elevated plasma tryptophan) could cause dysregulation of the inflammatory response that is intrinsic to normal pregnancy. This may contribute to the pathogenesis of the maternal syndrome of preeclampsia.